On the Cluster Formation of α-Synuclein Fibrils - Dubackic, Marija; Idini, Ilaria; Lattanzi, Veronica; Liu, Yun; Martel, Anne; Terry, Ann; Haertlein, Michael; Devos, Juliette M.; Jackson, Andrew; Sparr, Emma; Linse, Sara; Olsson, Ulf (Frontiers in Molecular Biosciences, 2021)
The dense accumulation of α-synuclein fibrils in neurons is considered to be strongly associated with Parkinson’s disease. These intracellular inclusions, called Lewy bodies, also contain significant amounts of lipids. To better understand such accumulations, it should be important to study α-synuclein fibril formation under conditions where the fibrils lump together, mimicking what is observed in Lewy bodies. In the present study, we have therefore investigated the overall structural arrangements of α-synuclein fibrils, formed under mildly acidic conditions, pH=5.5, in pure buffer or in the presence of various model membrane systems, by means of small-angle neutron scattering (SANS). At this pH, α-synuclein fibrils are colloidally unstable and aggregate further into dense clusters. SANS intensities show a power law dependence on the scattering vector, q, indicating that the clusters can be described as mass fractal aggregates. The experimentally observed fractal dimension was d = 2.6 ± 0.3. We further show that this fractal dimension can be reproduced using a simple model of rigid-rod clusters. The effect of dominatingly attractive fibril-fibril interactions is discussed within the context of fibril clustering in Lewy body formation.